High Anxiety: Addressing Family Issues in the Transition of Students with Disabilities from Middle Grades to High School - Brigham, Nancy; Aguilar, Cynthia M. (Journal of the American Academy of Special Education Professionals, 2011)
This article documents the development of a protocol that addresses the anxieties and tensions felt by the families of students with disabilities when they face the daunting transition from middle grades to high school. The tool grew out of a study of schools that form meaningful partnerships with diverse families of students with disabilities, funded by the U.S. Department of Education, Office of Special Education Programs (OSEP). The article details the process of developing the transition protocol, which is based on the real life experiences of families involved in the study and their experiences with transition. It expresses the families’ fears for the social and academic success of their children and how schools can help to counter these. The complete protocol, including assistance with logistics, a sample list of topics for the session and a scripted guide for facilitators are available free of change from the Inclusive School Network.